Synergistic removal of dyes by Myrothecium verrucaria immobilization on a chitosan–Fe membrane1. Issue 83 (9th September 2015) - Wen, Yuezhong; Liang, Ying; Shen, Chensi; Wang, Hongkai; Fu, Dongmei; Wang, Hongyu
<x xml:space="preserve">Abstract</x> A kind of novel, environmental friendly and efficient hybrid for the fungus and chitosan–Fe membrane has been fabricated by the alginate approach for efficient removal of aqueous dyes.